Estudo da relação entre a densidade do osso cortical e a progressão da calcificação coronariana em pacientes com doença renal crônica. - Rodrigues, Larissa Dias Biolcati [UNIFESP] (2019)
Background: Loss of trabecular bone has been associated with vascular calcification progression in chronic kidney disease (CKD) patients. There are few data evaluating the relationship between cortical bone and vascular calcification in this population. Objectives: The aim of this study was to prospectively evaluate the association between changes of cortical bone density and coronary artery calcification progression in non-dialyzed CKD patients. Methods: Post hoc analysis of changes of cortical and trabecular bone, and changes of calcium score, using vertebral tomographic images, during 24 months. Cortical and trabecular bone layer were evaluated by Image J® and Vitrea 2® software, respectively. Cortical and trabecular bone density (BD) were expressed in Hounsfield Units (HU), and coronary artery calcium score in Agatston Units (AU). Results: 70 asymptomatic patients [57.8 ± 10.2 years, 63% males, 20% diabetic, estimated glomerular filtration rate (eGFR) = 37.3 (24.8 – 51.3) mL/min/1.73m2 ] were evaluated. The mean cortical and trabecular BD did not change over time. While 49 patients lost either bone, 29 (41%) patients lost cortical [-4.4%/year (ranging from -7.15 to -0.5)] and 39 (56%) lost trabecular bone [-3.15%/year (-13.7 to -0.25)]. There was no association between cortical and trabecular BD changes (p=0.12). Coronary artery calcification was observed in 33 (46%) patients at baseline, and 30 (91%) of them showed progression. While an inverse correlation between trabecular bone and calcium score changes was observed (p=0.001), there was no correlation between cortical bone and calcium score changes (p=0.34). Conclusion: CKD patients experience either cortical or trabecular bone loss over time, but these changes do not take place simultaneously in all patients. Cortical unlike trabecular bone loss is not associated to vascular calcification progression in these patients.